Training, Motivation, and Environment: Boosting Contractor Work Productivity: Pelatihan, Motivasi Kerja, dan Lingkungan Kerja: Meningkatkan Produktivitas Kerja Kontraktor - Parlinda Parlinda; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aims to examine the influence of job training, work motivation, and work environment on employee work productivity in the context of CV. Budi Mulia, a leading cracker manufacturing company. The research employed a Non-Probability Saturated Sampling Technique, gathering data from 80 employees. Multiple linear regression analysis was conducted using SPSS Statistics version 25. The findings indicate that job training, work motivation, and work environment significantly affect employee work productivity. Notably, the work environment emerged as the most influential factor positively impacting employee productivity. This study sheds light on the importance of optimizing the work environment to enhance overall performance, offering implications for managers and organizations seeking to maximize their workforce potential. Highlights: The study examines the impact of training, motivation, and work environment on employee performance. The work environment emerged as the most influential factor positively affecting employee productivity. Optimizing training programs, fostering motivation, and creating a conducive work environment are crucial for enhancing employee performance. Keywords: Employee Performance, Training, Motivation, Work Environment, Productivity